Roberto Burle Marx: a contribuição do artista e paisagista no Estado de São Paulo - Guimarães, Marília Dorador (2011)
The theme of this research is the work of Roberto Burle Marx (1909-1994), a landscape artist. The research intends to analyze the production of its landscaping projects, which includes public and private gardens in the State of São Paulo. At first, the project seeks to note the artistic development of the landscape made by Roberto Burle Marx, highlighting importance of his intellectual development and references to other artists. Through his landscaping, Burle Marx puts together his artistic vein with his practical knowledge of the landscape elements. Even after studying in Europe, Burle Marx makes his dialogue with the Brazilian environment explicit in his work; his empirical knowledge, carved by the ideals of the modernity, generates a landscape that dwells on legitimacy